Correcting thrombin generation ex vivo using different haemostatic agents following cardiac surgery requiring the use of cardiopulmonary bypass. Issue 4 (June 2015) - Percy, Charles L.; Hartmann, Rudolf; Jones, Rhidian M.; Balachandran, Subramaniam; Mehta, Dheeraj; Dockal, Michael; Scheiflinger, Friedrich; O'Donnell, Valerie B.; Hall, Judith E.; Collins, Peter W.
Abstract : Recently, lower thrombin generation has been associated with excess bleeding post-cardiopulmonary bypass (CPB). Therefore, treatment to correct thrombin generation is a potentially important aspect of management of bleeding in this group of patients. The objective of the present study was to investigate the effects of fresh frozen plasma (FFP), recombinant factor VIIa (rFVIIa), prothrombin complex concentrate (PCC) and tissue factor pathway inhibitor (TFPI) inhibition on thrombin generation when added ex vivo to the plasma of patients who had undergone cardiac surgery requiring CPB. Patients undergoing elective cardiac surgery were recruited. Blood samples were collected before administration of heparin and 30 min after its reversal. Thrombin generation was measured in the presence and absence of different concentrations of FFP, rFVIIa, PCC and an anti-TFPI antibody. A total of 102 patients were recruited. Thrombin generation following CPB was lower compared with pre-CPB (median endogenous thrombin potential pre-CPB 339 nmol/l per min, post-CPB 155 nmol/l per min, P < 0.0001; median peak thrombin pre-CPB 35 nmol/l, post-CPB 11 nmol/l, P < 0.0001). Coagulation factors and anticoagulants decreased, apart from total TFPI, which increased (55–111 ng/ml, P < 0.0001), and VWF (144–170 IU/dl, P < 0.0001). Thrombin generation was corrected to pre-CPB levels by the equivalent of 15 ml/kg FFP, 45 μg/kg rFVIIa and 25 U/kg of PCC. Inhibition of TFPI resulted in an enhancement of thrombin generation significantly beyond pre-CPB levels. This study shows that FFP, rFVIIa, PCC and inhibition of TFPI correct thrombin generation in the plasma of patients who have undergone surgery requiring CPB. Inhibition of TFPI may be a further potential therapeutic strategy for managing bleeding in this group of patients.